Verificação e utilização de dados de relatórios ambientais na elaboração de inventários do ciclo de vida - Klemann, Liliane (2012)
With the growing concern about the environmental issue, not only the society, but also companies are seeking a balance, so that the economic, environmental and social interact harmoniously. Among the tools used for this purpose, the Life Cycle Assessment (LCA) has been highlighted because it allows evaluating the environmental impacts of an offered product or service. The LCA consists of four phases: goal and scope definition; inventory analysis; impact assessment; and, interpretation. Among these phases, the inventory analysis, which mainly consists of data collection, is the most time-consuming and perhaps the most difficult phase because of its length. Moreover, environmental data are available in environmental reports, by environmental agencies, by companies that can possibly be used. This study aims to determine the possibility of using the data from these environmental reports to help the development of Life Cycle Inventories (LCIs). To perform this check were established some criteria for cutting and quality that must be met and, if so, adequate these data for being used in LCIs. Three case studies were performed in which the verification and the adequacy to be used in LCIs were carried out. As a result, it can be stated that by following the procedure adopted in this work is possible to use the data from these environmental reports. Moreover it was found that most of these data environmental reports do not meet the minimum required for use in LCIs.